Optimized Thermal Simulation Model of Multilayer Printed Circuit Board - Frivaldsky, Michal; Spanik, Pavol; Morgos, Jan; Glapa, Norbert (Communications - Scientific letters of the University of Zilina, 2018)
Very thin multi-layers of Cu and epoxy compound in PCB (printed circuit board) make difficult to design computational meshes in finite element method simulation programs. Number of degrees of freedom in simulated system rapidly increases – it significantly extends simulation computational time. In this paper we propose substitution of the PCB in axial and radial direction with the composite structure with equivalent physical parameters of multilayer PCB.